The variation in pressures exerted by commercially available compression garments - Hill, J. A.; Howatson, G.; van Someren, K. A.; Davidson, S.; Pedlar, C. R. (Sports Engineering, 2015)
Commercially available compression garments (CGs) demonstrate the enhanced recovery from exercise in some, but not all studies. It is possible that in some cases the degree of compression pressure (ComP) exerted is not sufficient to produce any physiological benefit. The aim of this investigation was to identify the levels of ComP exerted by commercially available CGs. This study was composed of two parts. In part A 50 healthy, physically active individuals (n = 26 male, n = 24 female) were fitted with CGs according to manufacturer`s guidelines. ComP was measured in participants standing in the anatomical position with a pressure measurement device inserted between the skin and the garment. Data were compared to `ideal` pressure values proposed in the literature. In part B, ComP in three different brands of CG was compared in a population of 29 men who all wore a medium-sized garment. A one-way ANOVA indicated that there was a significant difference (P P > 0.05) between observed and ideal pressures in the calf of the male population. No significant differences in pressure (P > 0.05) were observed between CG brands at the quadriceps or calf. In conclusion, a large number of individuals may not be experiencing an adequate ComP from CG, and this is true for all the three major brands of CGs tested in this investigation.